Homoeopathic Treatment in Bilateral Pleural Effusion - Case Report (Advancements in Homeopathic Research, 2022)
The accumulation of fluid in the area between the layers of tissue that line the lungs and the chest cavity is referred as Pleural effusion. Objectives - To observe the efficacy of potentized homoeopathic medicine during treatment of a case of pleural effusion. Methods- A 50yrs old female patient Ms. D presented with pleural effusion which was confirmed by skiagraphy of the chest (mild to moderate collection of fluid in both side of pleural sac). After proper case recoding & analysis of symptoms of the patient the simillimum was selected as per homoeopathic principle & philosophy. The follow-up was done methodically. Results – After treatment skiagraphy of chest revels the gradual diminution & disappearance of fluid from pleural sac with eradications of all symptoms of the patient. Conclusion- The treatment shows efficacy of potentized Homoeopathic medicine in a case of pleural effusion.
Keywords: Pleural effusion; Potentized homoeopathic medicine; Skiagraphy